Authorship, plagiarism and conflict of interest: views and practices from low/middle-income country health researchers. Issue 11 (22nd November 2017) - Rohwer, Anke; Young, Taryn; Wager, Elizabeth; Garner, Paul
Abstract : Objectives: To document low/middle-income country (LMIC) health researchers' views about authorship, redundant publication, plagiarism and conflicts of interest and how common poor practice was in their institutions. Design: We developed a questionnaire based on scenarios about authorship, redundant publication, plagiarism and conflicts of interest. We asked participants whether the described practices were acceptable and whether these behaviours were common at their institutions. We conducted in-depth interviews with respondents who agreed to be interviewed. Participants: We invited 607 corresponding authors of Cochrane reviews working in LMICs. From the 583 emails delivered, we obtained 199 responses (34%). We carried out in-depth interviews with 15 respondents. Results: Seventy-seven per cent reported that guest authorship occurred at their institution, 60% reported text recycling. For plagiarism, 12% of respondents reported that this occurred 'occasionally', and 24% 'rarely'. Forty per cent indicated that their colleagues had not declared conflicts of interest in the past. Respondents generally recognised poor practice in scenarios but reported that they occurred at their institutions. Themes identified from in-depth interviews were (1) authorship rules are simple in theory, but not consistently applied; (2) academic status and power underpin behaviours; (3) institutions and culture fuel bad practices and (4) researchers are uncertain about what conflict of interests means and how this may influence research. Conclusions: LMIC researchers report that guest authorship is widely accepted and common. While respondents report that plagiarism and undeclared conflicts of interest are unacceptable in practice, they appear common. Determinants of poor practice relate to academic status and power, fuelled by institutional norms and culture.